Fostering citizen participation and sense of community through the project-oriented problem-based learning - Alwi, Azlin (2018)
In a world where there is a rise in mental health problems affecting the community, so too is the demand for psychologists to help manage these issues. However, problems cannot be solved by knowing the theory alone. It thus becomes important for psychology students to be skilled not only in their foundational knowledge but also their ability to solve these issues, and become the champion to initiate change within the society. Integrating these aspects into psychology education is certainly requires innovative approaches. This paper examines citizenship participation and sense of community through the implementation of project-oriented problem based learning (POPBL). The research question aims to answer whether there is a significant change in participants’ (1) perception of teaching and learning, (2) active and engaged citizenship, and (3) sense of community following participation in the POPBL approach. Using a purposive sampling, seventy three undergraduate students participated in this study. Three measures were used (pre and post) to gauge students’ perception during their engagement with the POPBL project. Those scales were (1) Students’ Perception of Teaching and Learning of the Course, (2) Active and Engaged Participation; and (3) Sense of Community Index. The results of paired samples t-tests show that the POPBL project improved students’ perception of teaching and learning, participation in citizenship (specifically civic skills and civic participation) and sense of community (membership, influence and shared emotional connection). The findings are also discussed in relation to the concept of sustainable development.